2007
DOI: 10.1523/jneurosci.0608-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Activation via Tyrosine Phosphorylation of Inhibitor κB-α Is Crucial for Ciliary Neurotrophic Factor-Promoted Neurite Growth from Developing Neurons

Abstract: The cytokine ciliary neurotrophic factor (CNTF) promotes the growth of neural processes from many kinds of neurons in the developing and regenerating adult nervous system, but the intracellular signaling mechanisms mediating this important function of CNTF are poorly understood. Here, we show that CNTF activates the nuclear factor-B (NF-B) transcriptional system in neonatal sensory neurons and that blocking NF-B-dependent transcription inhibits CNTF-promoted neurite growth. Selectively blocking NF-B activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 26 publications
2
67
0
Order By: Relevance
“…In agreement with this, we found that CD3 recruitment by a CD3 antibody induced an elevation of [Ca 2ϩ ] i in cultured neurons. The expression of ZAP-70 -related tyrosine kinase in developing neurons (Ishijima et al, 1995;Yoneya et al, 1998), and the reported role of Syk in neurite outgrowth (Tsujimura et al, 2001;Gallagher et al, 2007) is compatible with the notion that Syk/ZAP-70 could be a relevant component of the intracellular transduction pathway connecting CD3 activation and Ca 2ϩ mobilization to negatively control dendritic shaping.…”
Section: Potential Mechanisms For Cd3 Neuronal Functionsupporting
confidence: 75%
“…In agreement with this, we found that CD3 recruitment by a CD3 antibody induced an elevation of [Ca 2ϩ ] i in cultured neurons. The expression of ZAP-70 -related tyrosine kinase in developing neurons (Ishijima et al, 1995;Yoneya et al, 1998), and the reported role of Syk in neurite outgrowth (Tsujimura et al, 2001;Gallagher et al, 2007) is compatible with the notion that Syk/ZAP-70 could be a relevant component of the intracellular transduction pathway connecting CD3 activation and Ca 2ϩ mobilization to negatively control dendritic shaping.…”
Section: Potential Mechanisms For Cd3 Neuronal Functionsupporting
confidence: 75%
“…Here we show for the first time that NF-B is one of the central survival pathways of embryonic spinal cord MNs. It is also known that NF-B activity is related to other neuronal functions such as neurite outgrowth (Gallagher et al, 2007;Gutierrez et al, 2008), suggesting an important role of this pathway in neuronal development and probably in some neuronal diseases (Mattson and Meffert, 2006). For example, genes regulating NF-B pathway activity have been related to a novel form of lower motor neuron disease (Maystadt et al, 2007), indicating that indirect NF-B deregulation might be involved in neuronal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, NTFs can also activate other pathways that are crucial for the neuronal physiology. In some neuronal populations, the NF-B pathway is activated by cytokines and is responsible for cell survival and/or neurite outgrowth (Maggirwar et al, 1998;Gallagher et al, 2007). Because no information exists about the involvement of the NF-B pathway mediating MN survival, we decided to analyze this subject in our MN model.…”
Section: Neurotrophic Factor Stimulation Induces Nf-b Pathway Activatmentioning
confidence: 99%
See 1 more Smart Citation
“…LIGHT has multiple functions in the immune system and has been implicated in the regulation of cell proliferation and survival in several tissues and organs (Ware, 2005;Murphy et al, 2006;Pierer et al, 2007), but has no known role in the nervous system. HVEM and LT␤R lack death domains and interact with adaptors of the TRAF family to modulate several signaling pathways including the NF-B transcription family (Grivennikov et al, 2006), which has been implicated in regulating neurite growth from neonatal nodose ganglion neurons (Gutierrez et al, 2005;Gallagher et al, 2007). Here we report a novel function for LIGHT as a negative regulator of neurite growth in nodose sensory neurons by a mechanism involving the HVEM receptor and NF-B signaling inhibition.…”
Section: Introductionmentioning
confidence: 84%